Kecerdasan Emosional Tokoh Utama dalam Novel Kado Terbaik Karya J. S. Khairen Kajian Psikologi Sastra - Nurintani, Denanti; Israhayu, Eko Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research examines the emotional intelligence found in the main character in the novel Kado Best by J.S. Khairen using a literary psychology approach. The aim of this research is to describe the description of emotional intelligence experienced by the main character using qualitative methods. The data taken is in the form of words, sentences, paragraphs, quotations and dialogues contained in the novel Best Gift by J.S. Khairen which contains signs of emotional intelligence in the main character. The data collection technique used is the reading and note taking technique. The data analysis technique used is (1) listening carefully and reading repeatedly the data to be studied; (2) identifying data that contains emotional intelligence in the main character; (3) classifying data according to the focus of emotional intelligence problems according to Daniel Goleman; (4) note down the parts related to emotional intelligence; (5) analyze the data that has been recorded in accordance with the sub-focus problem that has been determined; (6) examine the data using triangulation theory and observer persistence. The results of the research show that there is emotional intelligence in the character Rizki, namely in the form of recognizing one's emotions, managing emotions, motivating oneself, motivating others, and building relationships